Review and Evaluation of Power Devices and Semiconductor Materials Based on Si, SiC, and Ga-N. (16th May 2022) - Ramkumar, M. Siva; Priya, R.; Rajakumari, R. Felshiya; Valsalan, Prajoona; Chakravarthi, M. Kalyan; Latha, G. Charlyn Pushpa; Mathupriya, S.; Rajan, Kavitha
Abstract : There is no reservation that semiconductor equipment distorted the world despite the fact of doing the practical experiments and also in research field. Researchers will communicate the process of semiconductor statistics with nearby pupils. In this work, diverse brand of semiconductor equipment was thrashed out with elementary properties and their distinctiveness. One type of semiconductor is differentiated based on energy band gap with an added type of semiconductor equipment. Semiconductor resources are the edifice block for the electrical and electronics component. This work makes an available apt generic argument of materials with the latest discussion and its impact of temperature on different materials, and it also reveals dissimilar parameters such as modern density, porch voltage value, transmission rate, and drain resistance value. Exceptional applications were discussed for divergent semiconductor materials.